The Public Becomes Personal: From Ernaux's Passion simple to Journal du dehors - Michelle Scatton-Tessier (Studies in 20th & 21st Century Literature, 2005)
Drawing on an interview in April 1997 with contemporary French writer Annie Ernaux, this article analyzes the interplay between female narrators and quotidian spaces in Passion simple (1991) and Journal du dehors (1993). Ernaux's writing career, spanning nearly thirty years, develops continually from depictions of physical spaces and the gestures or attitudes these spaces prescribe. Ernaux's spaces are not neutral; each bears the strong markings of a specific social class and gender. As this study illustrates, a radical shift exists between the author's 1991 and 1993 texts. Here, she distances herself from the traditional domestic space, as depicted in Passion simple, and concentrates on movement with the French capital and its environs in Journal. This shift leads to an inquiry into her narrators' compatibility with possible versions of the literary figures of the flâneur, as recorder of the modern city, and of the urban female wanderer, the flâneuse, as bourgeois shopper or prostitute. It also demonstrates the extent to which the author draws consistently on her personal preoccupations while expanding her scope to include a more journalistic approach to (auto)biographical texts.
Keywords: female narrators; quotidian space; passion simple; interview; jounal du dehors; Annie Ernaux; space; social class; gender; (auto)biography